2018
DOI: 10.1007/s12028-018-0536-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Prognosis of Severe Anti-N-methyl-d-aspartate Receptor Encephalitis Patients

Abstract: Most severe anti-NMDAR encephalitis patients will eventually achieve good long-term prognoses after receiving early, positive and unremitting combined immunotherapy and life support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 32 publications
4
36
3
Order By: Relevance
“…Previous studies have indicated that the parietal aEEG bandwidth may separate patients with favorable and poor long-term outcomes in the early disease stages (24). In our study, the first available EEG findings that obtained before immunotherapy showed generalized slowing in 14/18 patients (77.7%), focal slowing in 2/18 patients (11.1%), and no abnormalities in 2/18 patients (11.1%), consistent with the findings of previous reports (25, 26). No patients exhibited abnormal background activity at the final follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have indicated that the parietal aEEG bandwidth may separate patients with favorable and poor long-term outcomes in the early disease stages (24). In our study, the first available EEG findings that obtained before immunotherapy showed generalized slowing in 14/18 patients (77.7%), focal slowing in 2/18 patients (11.1%), and no abnormalities in 2/18 patients (11.1%), consistent with the findings of previous reports (25, 26). No patients exhibited abnormal background activity at the final follow-up.…”
Section: Discussionsupporting
confidence: 92%
“…Patients with anti-NMDAR encephalitis in our study demonstrated a lower incidence in women, with tumors, central hypoventilation, and a better prognosis, and this is consistent with the results of previous studies in China. 16 18 There was no sex difference, but a tendency to women was found. The prevalence of tumors was also lower in the Korean population than in the Western study populations.…”
Section: Discussionmentioning
confidence: 85%
“…Although AAG is an autoimmune disorder that causes autonomic dysfunction responsive to IVIg, it was considered unlikely because it causes postganglionic autonomic failure, and nearly half of AAG cases are positive for anti-ganglionic ACh receptor antibody (6). In some types of encephalitis, such as anti-NMDAR encephalitis and anti-GAD encephalitis, autonomic dysfunction can be induced by the impairment of the subthalamus or brainstem (7)(8)(9). However, these antibodies were negative.…”
Section: Discussionmentioning
confidence: 99%